Granuloma faciale successfully treated with ingenol mebutate. Issue 5 (30th June 2016) - Bobyr, I.; Campanati, A.; Consales, V.; Giangiacomi, M; Diotallevi, F.; Offidani, A.
ABSTRACT: Granuloma faciale (GF) is a rare chronic inflammatory dermatosis of unknown etiology, characterized by leukocitoclastic vasculitis usually occurring on the face. We report a case of 60‐years‐old man with 3 year history of multiple actinic keratoses (AK) and persistent asymptomatic erythematous papules and plaques located over his left temporal region and the cheek: histopathology was consistent with GF. Herein we describe the successful treatment of the lesion with ingenol mebutate 0.015% gel focusing on the clinical, dermoscopic and histopathological findings of GF both before and after treatment.